Effects of the COVID-19 pandemic on preschool children and preschools in Portugal. Journal - Cordovil, Rita (2021)
Problem Statement:The COVID-19 pandemic led to significant changes in the life routines of preschool children, both during lockdown and post-lockdown periods. Approach:An online survey completed by parents, in-loco assessment scales filled in by a researcherand semi-structured interviews with preschool teacherswere used to investigate the effects of the adjustments, which occurred in preschool children’s lives, in the lockdown and post lockdown periods.Purpose:To characterize the levels of physical activity that Portuguese children had during the lockdown period and to understand what changed in their school routines in the post-lockdown period, regarding the organization of school spaces and routines.Results:Parents reported that children aged 3 to 5spent most of their time during lockdownundertaking sedentary activities (72% of their daily activities). In the post-lockdown period,results indicate that in June there was an increase in the number of preschools with a poor quality of environment compared to the pre-pandemic period (October/November).Taking into account the measures implemented in preschools to prevent the COVID-19 transmission,teachers were of the opinion that limiting the number of children sharing material was the worst measure imposed, since it hampered children’s socialization. Conversely, increasing the use of the outdoor space was deemed positive because it improved children’s happiness and action possibilities outside.Conclusions: TheCOVID-19pandemic has had a clear impact on Portuguese children’s overall levels of physical activity during lockdown. In some schools, the implementation of health guidelines has also led to further negative effects on children’s play opportunities. However, many schools seem to be successful in finding strategies to ensure a healthy balance between promoting children’s physical activity and ensuring risk control.